Adaptive backstepping robust tracking control for stabilizing lateral dynamics of electric vehicles with uncertain parameters and external disturbances. (May 2021) - Pang, Hui; Yao, Rui; Wang, Peng; Xu, Zijun
Abstract: This paper presents a composite adaptive backstepping robust tracking controller which aims to improve the lateral dynamics stability for an electric vehicle (EV) while considering the uncertain parameters and external disturbances. First, a nonlinear three degree-of-freedom vehicle model is built up to describe the lateral and roll dynamics behaviors of this EV. Then, the projection adaptive control law is developed by combining adaptive backstepping and dynamic surface control techniques, which is expected to make the sideslip angle and the yaw rate approaching the ideal ones as closely as possible. The sufficient conditions for designing such a controller are also derived in the framework of Lyapunov theory to guarantee its asymptotical stability, thus the desirable controller design is devised. Finally, a comparative CarSim–Simulink joint simulation is carried out to verify the effectiveness of the proposed controller under single-lane-change and J-turn maneuvers. Highlights: Based on an established 3-DOF dynamics model, a desirable ABRTC is proposed for stabilizing lateral dynamics of EVs in the presence of uncertain parameters and external disturbances. The DSC technology is employed to estimate the derivatives of the virtual control law, meanwhile a robust feedback term of yaw moment is included. Then, the big-bang complexity can be avoided. By employing the designed virtual control inputs, a projection-based control law is derived, and the stability analysis of the proposed ABRTC is analyzed.